1998
DOI: 10.1002/jppr1998283174
|View full text |Cite
|
Sign up to set email alerts
|

Nasogastric Administration of Omeprazole

Abstract: A section for the publication of questions and responses of current interest from drug information centres.Submissions are reviewed by the Journal's editors but are not usually reviewed externally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Dispersible tablets are an option but cannot be used via fine bore tubes. 4,5 An audit at the Sydney Children's Hospital found that around 9% of all inpatients were prescribed omeprazole and 85% needed a liquid formulation. 6 The Sydney Children's Hospital pharmacy department prepares 12 L of omeprazole liquid formulation per month and the Royal Children's Hospital, Melbourne prepares 2 L of omeprazole suspension each working day.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersible tablets are an option but cannot be used via fine bore tubes. 4,5 An audit at the Sydney Children's Hospital found that around 9% of all inpatients were prescribed omeprazole and 85% needed a liquid formulation. 6 The Sydney Children's Hospital pharmacy department prepares 12 L of omeprazole liquid formulation per month and the Royal Children's Hospital, Melbourne prepares 2 L of omeprazole suspension each working day.…”
Section: Introductionmentioning
confidence: 99%